Mediating Effect of Chronic Illnesses in the Relationship Between Psychological Distress and COVID-19 Vaccine Acceptance. (January 2022) - Chen, Won Sun; Siau, Ching Sin; Bono, Suzanna Awang; Low, Wah Yun
The impact of the COVID-19 pandemic on mental health is an emerging problem globally. This study aimed to examine the mediating effect of chronic illnesses in the relationship between psychological health and the acceptance of the COVID-19 vaccine, prior to the national vaccine rollout in Malaysia. An online cross-sectional study was conducted in Malaysia between December 10, 2020, and February 9, 2021. In addition to the descriptive analyses, a mediation analysis was performed to examine the mediating effect of chronic illnesses in the relationship between psychological distress and the willingness to accept the vaccine. A total of 1738 participants completed the survey. The psychological distress levels were found to be significantly different across demographic factors such as age, gender, and social economic status. This study demonstrated a partial mediating effect of chronic illnesses in the relationship between psychological distress and vaccine acceptance.